2007
DOI: 10.1007/s10384-006-0433-y
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Retinal Nerve Fiber Layer Thickness and Macular Volume for Glaucoma Detection Using Optical Coherence Tomography

Abstract: Both peripapillary RNFL thickness and macular volume were decreased even in the early stage of glaucoma. Average RNFL thickness had greater diagnostic power than macular volume.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
87
2
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(96 citation statements)
references
References 14 publications
5
87
2
2
Order By: Relevance
“…23 IC 95% 0,148-0,382). Table 2 shows the relationship between quadrantic and hemifield macular thickness parameters and the corresponding VF sensitivity loss.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…23 IC 95% 0,148-0,382). Table 2 shows the relationship between quadrantic and hemifield macular thickness parameters and the corresponding VF sensitivity loss.…”
Section: Resultsmentioning
confidence: 99%
“…Since Zeimer et al (14) proposed to use macular thickness as an indicator of glaucoma severity, several studies have investigated this idea using technologies to measure retinal thickness such as OCT (18)(19)(20)(21)(22)(23)(24) . Such studies were conducted based on the theory that the macular thickness might be superior to circumpapillary RNFL for quantification of axonal loss, because retinal ganglion cell bodies are 10 to 20 times the diameter of their axons and because the retinal ganglion cell layer is more than one cell thick in the macula (25) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results also provide new data that APAC results in a decrease in outer macular volume, though this was not associated with significant visual field defects or optic disc pallor. Earlier studies indicate that macular thickness is decreased in both paediatric 20,21 and adult glaucoma [22][23][24][25] patients. We found that macular RNFL loss in APAC eyes was mild and o10% compared with fellow eyes, hence was unlikely to be extensive enough to cause visual field defects on standard white-on-white perimetry.…”
Section: Discussionmentioning
confidence: 99%
“…Glaucoma diagnosis is made by using anterior chamber angle measurement. Retinal Nerve Fiber Layer (RNFL) thickness and macular volume is computed for glaucoma diagnosis using OCT images 6 . The variance analysis and Bonferroni's correction are used for determination of RNFL thickness and macular volume.…”
mentioning
confidence: 99%